2020
DOI: 10.3390/microorganisms8010089
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Stress-Inducing Treatments cause Distinct Aberrant Body Morphologies in the Chlamydia-Related Bacterium, Waddlia chondrophila

Abstract: Chlamydiae, such as Chlamydia trachomatis and Chlamydia pneumoniae, can cause chronic infections. It is believed that persistent forms called aberrant bodies (ABs) might be involved in this process. AB formation seems to be a common trait of all members of the Chlamydiales order and is caused by distinct stress stimuli, such as β-lactam antibiotics or nutrient starvation. While the diverse stimuli inducing ABs are well described, no comprehensive morphological characterization has been performed in Chlamydiale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…As due to the presence of efflux pumps in amoebae the treatment with drugs often requires higher concentrations than in mammalian cells, we chose to grow W. chondrophila in human (HEp-2) cells for the RNA-seq experiment. Moreover, we had already observed that BPDL induced the formation of ABs in W. chondrophila grown in Vero cells [29].…”
Section: Bpdl Treatment Induces the Formation Of Aberrant Bodies In Wmentioning
confidence: 80%
“…As due to the presence of efflux pumps in amoebae the treatment with drugs often requires higher concentrations than in mammalian cells, we chose to grow W. chondrophila in human (HEp-2) cells for the RNA-seq experiment. Moreover, we had already observed that BPDL induced the formation of ABs in W. chondrophila grown in Vero cells [29].…”
Section: Bpdl Treatment Induces the Formation Of Aberrant Bodies In Wmentioning
confidence: 80%
“…Aberrant bodies were first described in 1993 on Chlamydia cultured on McCoy cells and incubated in Eagle's minimal essential medium lacking all 13 amino acids [27]. Chlamydia AB formation is also induced in vitro by antibiotics (beta-lactam antibiotics, fosfomycin, novobiocin, fosmidomycin, and Azithromycin) [28][29][30][31][32][33]), depletion of essential nutrients (i.e., iron, amino acids, and glucose), heat shock, coinfection with Herpes Simplex virus [27,[34][35][36][37][38][39], infection of monocytes and macrophages [40][41][42], cytokines (Interferon-gamma and IFN-γ) [43], and a number of other pressures [44,45]. AB in certain Chlamydial species is also induced by treatment with LPC-011 (LPC), a potent inhibitor of the zinc-dependent cytoplasmic deacetylase LpxC, which catalyzed the first step in the Chlamydial Persistence in Chlamydia DOI: http://dx.doi.org/10.5772/intechopen.109299 lipooligosaccharide (LOS) biosynthesis pathway [46].…”
Section: Aberrant Bodiesmentioning
confidence: 99%

Persistence in Chlamydia

Scharbaai-Vázquez,
J. López Font,
A. Zayas Rodríguez
2023
Infectious Diseases
“…Transient exposure to 37 °C irremediably blocks the replication of R. porcellionis Members of the Chlamydiaceae are known to enter a third non-replicative stage, the aberrant body, when exposed to stresses such as antibiotic exposure (50), nutrient deprivation (51) or heat shock (52). Aberrant bodies are typically described as non-replicating enlarged cells able to resume their regular cycle once the stress disappears, although their morphology was shown to vary in function of the stresses (53,54). We thus wondered whether R. porcellionis could similarly recover and resume its growth cycle after an exposure to 37 °C.…”
Section: B) In Mammalian Cells Although the Doubling Time Was Signifi...mentioning
confidence: 99%